2019
DOI: 10.1038/s41598-019-46294-6
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Retinal Nerve Fibre Layer Segmentation Errors on Spectral Domain-Optical Coherence Tomography with a Deep Learning Algorithm

Abstract: In this study we developed a deep learning (DL) algorithm that detects errors in retinal never fibre layer (RNFL) segmentation on spectral-domain optical coherence tomography (SDOCT) B-scans using human grades as the reference standard. A dataset of 25,250 SDOCT B-scans reviewed for segmentation errors by human graders was randomly divided into validation plus training (50%) and test (50%) sets. The performance of the DL algorithm was evaluated in the test sample by outputting a probability of having a segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…Class activation maps (CAMs) 20 are a common method where a heat map is generated by projecting the class specific weights of the output classification layer back to the feature maps of the last convolutional layer, thereby highlighting important regions for predicting a particular class. This method has been used in ophthalmic application previously to confirm CNN decision was based off the anterior chamber angle in categorizing angle closure, 21 areas of OCT B-scans associated with various diagnoses 22 , 23 and areas of segmentation error, 24 and area of OCT enface images associated with the diagnosis of glaucoma. 25 There exists several variants of this method that build off of the original CAM paper, 20 including: Grad-Cam, 26 Guided Grad-Cam, 26 Guided Grad-Cam++, 27 and GAIN.…”
Section: Introductionmentioning
confidence: 99%
“…Class activation maps (CAMs) 20 are a common method where a heat map is generated by projecting the class specific weights of the output classification layer back to the feature maps of the last convolutional layer, thereby highlighting important regions for predicting a particular class. This method has been used in ophthalmic application previously to confirm CNN decision was based off the anterior chamber angle in categorizing angle closure, 21 areas of OCT B-scans associated with various diagnoses 22 , 23 and areas of segmentation error, 24 and area of OCT enface images associated with the diagnosis of glaucoma. 25 There exists several variants of this method that build off of the original CAM paper, 20 including: Grad-Cam, 26 Guided Grad-Cam, 26 Guided Grad-Cam++, 27 and GAIN.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, neural networks and other artificial intelligence (AI) algorithms have been shown to successfully model complex, nonlinear relationships in data from diverse medical fields. 8 12 In particular, convolutional neural networks (CNNs) are able to take advantage of spatial information to identify underlying relationships that may not be easily discerned by conventional methods. A few studies have attempted to use AI algorithms to predict visual field results from SDOCT measurements, with good results.…”
Section: Introductionmentioning
confidence: 99%
“…Artefacts and segmentation errors are highly prevalent on SDOCT and result in erroneous estimates of RNFL thickness [5][6][7]11,12 . While Asrani et al identified artefacts in 19.9% of RNFL circle scans 5 , Liu et al found at least one artefact in 46.3% of the 2,313 scans analysed in their study 6 .…”
Section: Discussionmentioning
confidence: 99%